2017
DOI: 10.1128/jcm.00970-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phenotypic and Genotypic Analysis of Edwardsiella Isolates from Different Hosts and Geographic Origins, with Emphasis on Isolates Formerly Classified as E. tarda, and Evaluation of Diagnostic Methods

Abstract: spp. are responsible for significant losses in important wild and cultured fish species worldwide. Recent phylogenomic investigations have determined that bacteria historically classified as actually represent three genetically distinct yet phenotypically ambiguous taxa with various degrees of pathogenicity in different hosts. Previous recognition of these taxa was hampered by the lack of a distinguishing phenotypic character. Commercial test panel configurations are relatively constant over time, and as new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 91 publications
4
125
1
1
Order By: Relevance
“…The genus Edwardsiella was composed by three species E. tarda , E. hoshinae, and E. ictaluri before 2013 (Abayneh, Colquhoun, & Sørum, ). Some strains of E. piscicida pathogenic to fish, previously identified as E. tarda , was described in 2013 (Abayneh, Colquhoun, & Sørum, ), and a new species named E. anguillarum , also previously identified as E. tarda , was isolated from diseased eel (Reichley et al, ). Until 2016, 13 strains of E. anguillarum isolated from diseased eels in our study were first identified as E. tarda (Duan, ; Hu, ), and then all 13 strains were identified as E. anguillarum according to the method of Buján et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Edwardsiella was composed by three species E. tarda , E. hoshinae, and E. ictaluri before 2013 (Abayneh, Colquhoun, & Sørum, ). Some strains of E. piscicida pathogenic to fish, previously identified as E. tarda , was described in 2013 (Abayneh, Colquhoun, & Sørum, ), and a new species named E. anguillarum , also previously identified as E. tarda , was isolated from diseased eel (Reichley et al, ). Until 2016, 13 strains of E. anguillarum isolated from diseased eels in our study were first identified as E. tarda (Duan, ; Hu, ), and then all 13 strains were identified as E. anguillarum according to the method of Buján et al ().…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of bacterial diseases is the common factor that affects Japanese eel production in China. Edwardsiella anguillarum , identified as Edwardsiella tarda before 2015 (Buján et al, ; Shao et al, ) and Vibrio vulnificus (Esteve‐Gassent, Nielsen, & Amaro, ; Haenen et al, ; Reichley et al, ) are two important bacterial pathogens in eels farming, and cause serious disease and high levels of mortality in cultured eels resulting in considerable economic losses in Chinese aquaculture (Guo, ; Guo et al, ; ). These two pathogens are also recognized as causing serious diseases in a variety of fish species globally (Griffin et al, ; Jheng et al, ; Lee et al, ; Shao et al, ; Tsao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary investigations identified multiple distinct taxa within organisms previously classified as E. tarda , each with varying pathogenicity in different hosts (Abayneh, Colquhoun, & Sørum, ; Griffin et al, ; Matsuyama, Kamaishi, Ooseko, Kurohara, & Iida, ; Wang et al, ; Yamada & Wakabayashi, ; Yang et al, ). This led to the erection of Edwardsiella piscicida (Abayneh, Colquhoun, & Sørum, ) and Edwardsiella anguillarum (Shao et al, ), which represent strains formerly categorized as typical and atypical fish pathogenic E. tarda , respectively (Buján et al, ; Reichley et al, ; Sakai, Yuasa, Sano, & Iida, ).…”
Section: Primer and Probe Sequencesmentioning
confidence: 99%
“…Since its recognition in 2013, E. piscicida has been reported from >20 species of economically and recreationally important fish (Reichley et al, ). Disease presentation varies among hosts, with a range of lesions often described as non‐specific signs of bacterial septicaemia (Griffin, Greenway, & Wise, ).…”
Section: Primer and Probe Sequencesmentioning
confidence: 99%
See 1 more Smart Citation